2015
DOI: 10.1007/s10877-015-9759-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurements of pulse pressure variation and stroke volume variation in anesthetized patients using the Nexfin blood pressure monitor

Abstract: Nexfin beat-to-beat arterial blood pressure monitoring enables continuous assessment of hemodynamic indices like cardiac index (CI), pulse pressure variation (PPV) and stroke volume variation (SVV) in the perioperative setting. In this study we investigated whether Nexfin adequately reflects alterations in these hemodynamic parameters during a provoked fluid shift in anesthetized and mechanically ventilated patients. The study included 54 patients undergoing non-thoracic surgery with positive pressure mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…For example, in the study of Stens J et al, Ea dyn was evaluated non-invasively with a finger plethysmography device (Nexfin R ) for predicting preloadresponsiveness after positioning the patient in Trendelenburg position. They found that the degree of fluid responsiveness was not associated with baseline Ea dyn values (Stens et al, 2016). Since Trendelenburg maneuvers will increase arterial pressure independent of flow, such negative results are predictable.…”
Section: Ea Dyn For Guiding Fluid Therapy In Hypotensive and Preload-mentioning
confidence: 98%
“…For example, in the study of Stens J et al, Ea dyn was evaluated non-invasively with a finger plethysmography device (Nexfin R ) for predicting preloadresponsiveness after positioning the patient in Trendelenburg position. They found that the degree of fluid responsiveness was not associated with baseline Ea dyn values (Stens et al, 2016). Since Trendelenburg maneuvers will increase arterial pressure independent of flow, such negative results are predictable.…”
Section: Ea Dyn For Guiding Fluid Therapy In Hypotensive and Preload-mentioning
confidence: 98%
“…Results of studies including ICU septic patients with acute circulatory failure and receiving vasopressors are very promising [13, 16, 17]. On the another hand, studies including operating room patients without vasopressor support and suffering from non-septic hypovolemia showed conflicting results [11, 12, 15, 18]. We can hypothesize that volume expansion induces different effects on arterial compliance in patients receiving vasopressors or not.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some previous studies, Trendelenburg position was performed to assess fluid responsiveness instead of volume expansion, and it has been demonstrated that this manoeuvre was effective to induce a relevant volume challenge. 29,30 Even with these methodological limitations, the current study revealed that deep breathing could improve the reliability of dynamic indices in spontaneously breathing patients. By means of deep breathing, SVV can be used as a simple bedside test to guide fluid management, even in patients with spontaneous breathing, eg before anaesthetic induction.…”
Section: Discussionmentioning
confidence: 75%
“…Instead, we induced volume shift by tilting the patients to the Trendelenburg position, which can be associated with false negative. However, in some previous studies, Trendelenburg position was performed to assess fluid responsiveness instead of volume expansion, and it has been demonstrated that this manoeuvre was effective to induce a relevant volume challenge …”
Section: Discussionmentioning
confidence: 99%